Vascular Organoids Derived from Capillary malformation-induced Pluripotent Stem Cells Exhibit Disease-Relevant Phenotypes - Vi Nguyen; Anna Harper; Mackenzie Azuero; Isabella Castellanos; Siwuxie He; Marcelo L. Hochman; Camilla F. Wenceslau; Dong-bao Chen; Anil G. Jegga; Yunguan Wang; Daping Fan; J. Stuart Nelson; et al. (Stem Cell Reviews and Reports, 2026)
Capillary malformation (CM) is a congenital vascular anomaly that affects the skin, mucosa, eye, and brain. A major obstacle to mechanistic and drug screening studies for CM has been the lack of preclinical models. In this study, we established vascular organoids (VOs) generated through the self-assembly of vascular lineages of endothelial cells and smooth muscle cells differentiated from CM-induced pluripotent stem cells (iPSC). Within these VOs induced endothelial cells and smooth muscle cells organized into juxtapositions to form vascular branches. CM patient iPSC-derived VOs showed a higher density of endothelial and smooth muscle cell populations and greater vascular branch lengths as compared with VOs derived from iPSCs generated from healthy skin biopsies. Overall, this study represents the first disease-relevant VO model of CM, providing a valuable platform for future mechanistic studies and drug screening.